Effects of the depletion of whey proteins from unconcentrated milk using microfiltration on the yield, functionality, and nutritional profile of Cheddar cheese - Reale, E; Govindasamy-Lucey, S; Johnson, M E; Jaeggi, J J; Molitor, M; Lu, Y; Lucey, J A (Journal of dairy science, 2020)
Some European dairies use low concentration factor microfiltration (MF) in their cheese plants. Removal of whey protein (WP) from milk before cheesemaking using microfiltration without concentration provides the opportunity to produce a value-added by-product, milk-derived whey. However, few studies have focused on the effects on cheese properties caused by the depletion of WP from cheese milk. Most studies have concentrated cheese milk using MF in addition to depletion of WP. In our approach, cheese milk was not concentrated during WP depletion using MF. We wanted to quantify residual WP levels in cheese made from MF milk and to explore whether WP depletion from milk would influence functionality, nutritional profile, and cheese quality during ripening. Casein (CN) contents for all milks were kept at ∼2.5%, to eliminate the confounding factor of concentration of CN, which was observed in some previous MF studies. Cheese milks had similar ratios of CN to fat. Three standardized milks were produced with various CN:true protein (TP) ratios: (a) control with a CN:TP ratio of 83:100, (b) 35% WP depletion, 89:100 CN:TP, and (c) 70% WP depletion, 95:100 CN:TP. Cheddar cheeses were made from MF milk with various WP depletion levels and aged for 9 mo, and their functionality was evaluated during ripening. We found no major differences in cheese composition or pH values between samples. Cheese yield, solids recovery, and nitrogen recovery were slightly higher in the 95:100 CN:TP cheeses compared with the control. These enhanced recoveries reflect that MF-treated milk started with a higher fraction of CN-based protein solids, rather than WP solids. The standardized milk from the 95:100 CN:TP treatment also had a slightly higher fat content compared with the control, likely helping to increase cheese yield. Rheological properties of cheeses during heating were similar between treatments. Hardness initially decreased with age for all cheeses due to proteolysis or solubilization, or both, of calcium phosphate. Maximum loss tangent (LT), an index of cheese meltability, was slightly lower for the control cheese until 30 d of ripening, but after 30 d, all treatments exhibited similar maximum LT values. The temperature where LT = 1 (crossover temperature), an index of softening point during heating, was slightly lower for MF cheese compared with the control cheeses during ripening. Microfiltration treatment had no significant influence on proteolysis. Sensory properties were similar between the cheeses, except for bitterness. Bitterness intensity was slightly lower in the MF cheeses than in the control cheeses and increased in all cheeses during ripening. We detected no major differences in the concentrations of key nutrients or vitamins between the various cheeses. Depletion of WP in cheese milk by MF did not negatively affect cheese quality, or its nutritional profile, and resulted in similar cheesemaking yields.